Daniel of St. Thomas Jenifer papers - Jenifer, Daniel of St. Thomas, 1723-1790.; Wallace, Charles, 1727-1812.
Transcript of a letter (undated) to Jenifer, Maryland intendant of the revenue, from Charles Wallace describing Wallace's financial problems as contractor for the construction of the Maryland State House in Annapolis. Transcribed on the verso of Jenifer's copy of a resolution by the U.S. Congress concerning state credit for personal debts incurred during the Revolution.
Handwritten transcript.
Maryland public official.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Previously cataloged under: Wallace, Charles, fl. 1784. Letter with resolution, 1784.
Keywords: Maryland. -- Intendant of the Revenue; Maryland State House (Annapolis, Md.); United States. -- Congress -- Resolutions; Public buildings -- Design and construction; Public buildings -- Maryland -- Annapolis; Maryland -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Claims; United States -- History -- Revolution, 1775-1783 -- Economic conditions; Public officials -- Maryland